Analisis Pengaruh Struktur Modal, Ukuran Perusahaan, dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Dian Melsa Irawati; Sri Hermuningsih; Alfiatul Maulida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study was to determine the effect of capital structure, firm size, and firm growth on firm value in the food and beverages industry sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This study uses quantitative research with sampling using purposive sampling method, which is a method of selecting samples with certain predetermined criteria. So that in this study, 51 data were obtained from 13 companies that met the criteria. The data analysis technique used is panel data analysis. The results of the study found that partially capital structure had a significant negative effect on firm value, firm size had a significant positive effect on firm value, and firm growth had no positive effect on firm value. Keywords : capital structure, company size, company growth, company value